Case Report: Minimally invasive removal of impacted supernumerary teeth using digital 3D-printed surgical guides: a case series - Chen, Qilin; Li, Zhiwei; Li, Zhenzhen; Xu, Wenpin; Yu, Zijing; Wang, Jian (Frontiers in Surgery, 2025)
The surgical management of impacted supernumerary teeth (ST) remains challenging because of their hidden position and close proximity to vital anatomical structures. These guides offered accurate intraoperative guidance and minimized both bone removal and soft-tissue dissection. A standardized digital workflow that integrates cone-beam computed tomography (CBCT) and intraoral scans was employed to create patient-specific guides that precisely dictated the osteotomy location. The guides provided critical intraoperative guidance and minimized the extent of bone removal and soft tissue dissection. This accurate and focused approach contributed to observed reductions in postoperative discomfort and swelling, supporting an overall favorable recovery profile in all cases. The application of 3D-printed surgical guides enables a highly precise and minimally invasive approach for the removal of impacted ST, thereby improving postoperative recovery. Furthermore, this technique shows considerable potential for broader application in oral and maxillofacial surgery by ensuring precise localization, reducing complications, and enhancing operative efficiency.